Chile : 2008 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chile. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that the Chilean economy has proved resilient in the face of strong economic and financial headwinds during the past year. Rising world prices for energy and food have been exacerbated by drought and a tight domestic energy situation. The government continues to move forward with a bold structural agenda. In the financial sector, the authorities plan to introduce initiatives aimed at enhancing market access for small and medium-sized enterprises, increase market depth, and boost the internationalization of the peso.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet